A rapid assessment of co-benefits and trade-offs among Sustainable Development Goals. (July 2018) - Singh, Gerald G.; Cisneros-Montemayor, Andrés M.; Swartz, Wilf; Cheung, William; Guy, J. Adam; Kenny, Tiff-Annie; McOwen, Chris J.; Asch, Rebecca; Geffert, Jan Laurens; Wabnitz, Colette C.C.; Sumaila, Rashid; Hanich, Quentin; et al.
Abstract: Achieving the United Nations' 17 Sustainable Development Goals (SDGs) results in many ecological, social, and economic consequences that are inter-related. Understanding relationships between sustainability goals and determining their interactions can help prioritize effective and efficient policy options. This paper presents a framework that integrates existing knowledge from literature and expert opinions to rapidly assess the relationships between one SDG goal and another. Specifically, given the important role of the oceans in the world's social-ecological systems, this study focuses on how SDG 14 (Life Below Water), and the targets within that goal, contributes to other SDG goals. This framework differentiates relationships based on compatibility (co-benefit, trade-off, neutral), the optional nature of achieving one goal in attaining another, and whether these relationships are context dependent. The results from applying this framework indicate that oceans SDG targets are related to all other SDG goals, with two ocean targets (of seven in total) most related across all other SDG goals. Firstly, the ocean SDG target to increase economic benefits to Small Island Developing States (SIDS) and least developed countries for sustainable marine uses has positive relationships across all SDGs. Secondly, the ocean SDG target to eliminate overfishing, illegal and destructive fishing practices is a necessary pre-condition for achieving the largest number of other SDG targets. This study highlights the importance of the oceans in achieving sustainable development. The rapid assessment framework can be applied to other SDGs to comprehensively map out the subset of targets that are also pivotal in achieving sustainable development. Highlights: A framework is presented to assess links in Sustainable Development Goals (SDGs). The Oceans goal (SDG 14) is related to all other SDGs. Increasing benefits to developing states generates the most co-benefits across SDGs. Ending overfishing is a pre-requisite for the most targets across SDGs.